Does Post-Activation Performance Enhancement (PAPE) occur with strength exercises on unstable surfaces? Effects on jump and sprint performance in a randomized crossover trial - Juan Sebastián Cardona Gómez; Andrés Rojas Jaramillo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The effect of Post-Activation Performance Enhancement (PAPE) has been investigated using various strength exercises and training equipment.